Protein methyltransferase 7 deficiency in Leishmania major increases neutrophil associated pathology in murine model - Alcoforado Diniz, Juliana; Chaves, Mariana M; Vaselek, Slavica; Miserani Magalhães, Rubens D; Ricci-Azevedo, Rafael; de Carvalho, Renan V H; Lorenzon, Lucas B; Ferreira, Tiago R; Zamboni, Dario; Walrad, Pegine B; Volf, Petr; Sacks, David L; et al. (PLoS neglected tropical diseases, 2021)
Leishmania major is the main causative agent of cutaneous leishmaniasis in the Old World. In Leishmania parasites, the lack of transcriptional control is mostly compensated by post-transcriptional mechanisms. Methylation of arginine is a conserved post-translational modification executed by Protein Arginine Methyltransferase (PRMTs). The genome from L. major encodes five PRMT homologs, including the cytosolic protein associated with several RNA-binding proteins, LmjPRMT7. It has been previously reported that LmjPRMT7 could impact parasite infectivity. In addition, a more recent work has clearly shown the importance of LmjPRMT7 in RNA-binding capacity and protein stability of methylation targets, demonstrating the role of this enzyme as an important epigenetic regulator of mRNA metabolism. In this study, we unveil the impact of PRMT7-mediated methylation on parasite development and virulence. Our data reveals that higher levels of LmjPRMT7 can impair parasite pathogenicity, and that deletion of this enzyme rescues the pathogenic phenotype of an attenuated strain of L. major. Interestingly, lesion formation caused by LmjPRMT7 knockout parasites is associated with an exacerbated inflammatory reaction in the tissue correlated with an excessive neutrophil recruitment. Moreover, the absence of LmjPRMT7 also impairs parasite development within the sand fly vector Phlebotomus duboscqi. Finally, a transcriptome analysis shed light onto possible genes affected by depletion of this enzyme. Taken together, this study highlights how post-transcriptional regulation can affect different aspects of the parasite biology.
Keywords: leishmanióza kožní; myši; delece genu; Protein Methyltransferases; regulace genové exprese enzymů; proteinmethyltransferasy; Leishmania major; zvířata; Mice; Neutrophils; Leishmaniasis, Cutaneous; Protozoan Proteins; protozoální proteiny; Gene Deletion; neutrofily; Gene Expression Regulation, Enzymologic; Animals